Atomic Decomposition of Weighted Lorentz Spaces and Operators. (13th April 2014) - Kwessi, Eddy; de Souza, Geraldo; Ngwane, Fidele; Abebe, Asheber
Abstract : We obtain an atomic decomposition of weighted Lorentz spaces for a class of weights satisfying the Δ2 condition. Consequently, we study operators such as the multiplication and composition operators and also provide Hölder's-type and duality-Riesz type inequalities on these weighted Lorentz spaces.